Social media as a medium for preventing radicalization (a case study of an Indonesian youth community’s counter-radicalization initiatives on Instagram) - Effendi, Ridwan; Sukmayadi, Vidi; Unde, Andi Alimuddin; Triyanto (2022)
Access online through this link: https://www.plarideljournal.org/article/social-media-as-a-medium-for-preventing-radicalization-a-case-study-of-an-indonesian-youth-communitys-counter-radicalization-initiatives-on-instagram
Keywords: Social media; Radicalism; Instagram (Web resource)